The existence of coprophilous macrofungi in Banyumas, Central Java, Indonesia: Coprophilous Macrofungi in Banyumas (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Mumpuni A, Ekowati N, Wahyono DJ. 2020. The existence of coprophilous macrofungi in Banyumas, Central Java, Indonesia. Biodiversitas 21: 282-289. Coprophilous fungi are cosmopolitan that inhabiting herbivorous animal feces. Some of them are edible mushrooms, as well as hallucinogenic psychotropic fungi that can be used in the pharmaceutical industry. Studies on coprophilous fungi in Indonesia have not been widely carried out. Tropical climate conditions in Indonesia including in the Ex- Residence of Banyumas, Central Java Province, Indonesia support the growth and spread of coprophilous fungi and are promoted by the spread of herbivorous livestock evenly in almost all regions that always provide suitable dung substrates for the fungal habitat. Based on this background, the purpose of this preliminary study was to obtain coprophilous fungi genera and find out their dominance in the area. This research used survey method with purposive random sampling and focused on macroscopic fungi. The obtained fungi were identified as macro and micro morphologically. From this study, there were 12 genera which were Panaeolus, Coprinopsis, Stropharia, Tricholoma, Lycoperdon, Ascobolus, Rhodocybe, Conocybe, Bolbitius, Leucocoprinus, Mycena, and Hypoloma. The dominance index of the coprophil fungal genera in the ex-residency Banyumas was 0.329; and the coprophil fungi obtained with the highest frequency of occurrence were Coprinopsis (34.4%) and Panaeolus (30.1%).
Keywords: Herbivorous animal feces fungi, Ex-Residence of Banyumas, dominance index